Effect of Career and Professional Development Course on Undergraduates’ Entrepreneurial and Professional Skills Development - Suglo, Kabinaa Enoch; Samuel Osei; Sherif Ziblim; Abubakari Mejira (Archives of Current Research International, 2025)
Many students enroll in higher education with little exposure to entrepreneurial and career development skills. This gap points out the need to equip undergraduates with professional and entrepreneurial competencies to enhance career readiness in this 21st century. This study aimed to assess the effect of career and professional development courses on undergraduate students’ professional and entrepreneurial skills. The study employed a quantitative approach and a descriptive design, guided by the Experiential Learning Theory. A census technique was used to consider 108 undergraduate students who had already been taken through career and professional development courses both in their first and second years of study. A closed-ended questionnaire developed via Google Form was used to collect data, with a response rate of 86.11%. The data collection instrument was piloted and validated, with Cronbach’s alpha coefficients ranging from 0.88 to 0.98. The results revealed a positive perception among the respondents that the career and professional development courses they have undertaken have a positive effect on their entrepreneurial and professional skills. The study concluded that career and professional development courses implemented by the university college aligned well with industry trends and students’ needs and were effective in enhancing their entrepreneurial and professional skills. The study recommended that higher educational institutions should consider introducing their undergraduates to similar career and professional development courses to help develop their entrepreneurial and professional skills.